Race-day temperature and marathon performance - analysing trends from six Olympic games (2004-2024) - Kumar, M. S.; Kurnaz, M.; Konar, N.; Grygus, I.; Sanjaykumar, S. (Journal of Human Sport & Exercise, 2025)
This study analysed the influence of race-day temperature on marathon performance over six Olympic Games (2004-2024), using data from the top 50 male and female finishers, resulting in 600 observations. Key variables included marathon finish times (minutes) and race-day temperatures (°C). Statistical methods such as paired t-tests and correlation analysis were employed to evaluate trends. Results show that marathon performances have steadily improved over time, with notable reductions in average times from 02:16:37 in Athens 2004 to 02:11:29 in Paris 2024. Key factors influencing these trends include advancements in training, hydration strategies, and equipment, as well as varying weather conditions. Optimal performance was observed in cooler temperatures, such as London 2012 (15.5°C) and Paris 2024 (19°C), while higher temperatures like in Beijing 2008 (26.5°C) and Tokyo 2020 (28.5°C) demonstrated heat-adaptive capabilities among athletes. Paired t-test comparisons revealed significant differences in performance across several Olympic years, with the largest improvements observed between 2012 and 2024 (mean difference: 00:03:10, p = .004). Pearson correlation analysis further highlighted a negative relationship between average marathon times and temperatures, indicating that cooler climates generally favour faster performances. The findings underscore the impact of weather conditions and technological advancements on marathon performance, providing valuable insights for athletes, coaches, and sports scientists aiming to optimize race strategies under varying environmental conditions.